The potential and limitations of radio as a health promotion tool: knowledge synthesis - Nascimento, Letícia Silva do; Ponte, Keila Maria de Azevedo; Couto, José Mário do; Sousa, Thaís Emmanuele Passos; Souza, Antonia Maria Ferreira de; Hipólito, José Janailson (Revista de Enfermagem da UFPI, 2024)
Objective: Identify the potential and limitations of using radio for health promotion. Methods: This is an integrative review carried out from September to November 2022, using the databases Latin American and Caribbean Literature in Health Sciences (LILACS), Nursing Database (Base de dados de Enfermagem, BDENF), National Library of Medicine (PUBMED) and Web of Science with the descriptors radio, information technology and health promotion. After the inclusion and exclusion criteria, a total of 16 articles remained. Results: As potentialities, it was identified that radio is a relevant tool for interaction and dissemination of information, as it manages to reach different audiences, enabling greater popular engagement and, consequently, greater effectiveness of health promotion actions. Its limitations include the complexity of certain subjects and the need to adapt the language used to the target audience. Conclusion: The conclusion is that health professionals should be empowered to use this technology as an intermediary tool for health education actions, since it enables greater interaction and brings the user-health professional-service relationship closer together.